Psychoanalysis on Conflict of the Main Character in TV Series Emily in Paris Season 2: Psychoanalytic Analysis - Gayatri, Ni Made; Aryawibawa, I Nyoman; Dewi, A.A. Sg. Shanti Sari (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2025)
This study aims to examine the character of Emily Cooper in the second season of the television series Emily in Paris from a psychoanalytic perspective. The focus of the research will be on Emily Cooper's problems and how Emily solves them. This study applies a qualitative methodology, as qualitative research mainly concerns qualitative phenomena. This study aims to determine how individuals feel or think about a particular issue or institution. The data of this study were collected by watching the television series on Netflix, screen shooting and then analyze descriptively. In addition, this research implements two theories: the first is from Sigmund Freud (1989), known as the model of the mind, and the second is from Kenney (1966), known as the forms of conflict. According to Sigmund Freud, there are three models of mind such as id, ego and superego. While Kenney classified the conflict into four, conflict within a single man, conflict between men, conflict between man and society, and conflict between man and nature. This study then determined that conflict within a single man, and conflict between men occurred most frequently in Emily Cooper's character. When Emily Cooper tries to solve a problem, her id, ego, and superego all play an important role. Keywords: Conflict, Psychoanalysis, Kenney, Sigmund Freud